2004
DOI: 10.1111/j.1462-2920.2004.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Pseudomonas putida phenanthrene‐degrading activity by plant root extracts and exudates

Abstract: The phenanthrene-degrading activity (PDA) of Pseudomonas putida ATCC 17484 was repressed after incubation with plant root extracts of oat (Avena sativa), osage orange (Maclura pomifera), hybrid willow (Salix alba x matsudana), kou (Cordia subcordata) and milo (Thespesia populnea) and plant root exudates of oat (Avena sativa) and hybrid poplar (Populus deltoides x nigra DN34). Total organic carbon content of root extracts ranged from 103 to 395 mg l(-1). Characterization of root extracts identified acetate (not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 53 publications
8
87
2
1
Order By: Relevance
“…The attraction of competent bacteria to the root zone may improve bioavailability and increase PAH degradation in the rhizosphere. Subjugation of the phenanthrene degrading activity of P. putida following exposure to root extracts and exudates recommended that enzyme induction may not occur during rhizodegradation of PAHs (Rentz et al, 2004). Related studies observed repression of PAH catabolic genes on a per cell basis and demonstrated greater naphthalene degradation by cultures grown on root products compared to naphthalene, supporting the notion that prolific microbial growth provides improved degradation in the rhizosphere (Kamath et al, 2004).…”
Section: Approaches Of Remediationmentioning
confidence: 53%
“…The attraction of competent bacteria to the root zone may improve bioavailability and increase PAH degradation in the rhizosphere. Subjugation of the phenanthrene degrading activity of P. putida following exposure to root extracts and exudates recommended that enzyme induction may not occur during rhizodegradation of PAHs (Rentz et al, 2004). Related studies observed repression of PAH catabolic genes on a per cell basis and demonstrated greater naphthalene degradation by cultures grown on root products compared to naphthalene, supporting the notion that prolific microbial growth provides improved degradation in the rhizosphere (Kamath et al, 2004).…”
Section: Approaches Of Remediationmentioning
confidence: 53%
“…There is scattered evidence indicating that, when confronted by mixtures of aromatic compounds in sufficient concentrations, some soil bacteria metabolize certain aromatics preferentially over others. For example, root extracts from several plants, which contain several aromatic compounds, can inhibit the assimilation of phenanthrene by a strain of P. putida (33). Similarly, benzoate inhibits the catabolism of phenol in Ralstonia eutropha (1) and represses 4-hydroxybenzoate degradation genes in P. putida (29).…”
Section: Vol 190 2008mentioning
confidence: 99%
“…C for 48 h and preserved in a refrigerator at À20 C. The procedure used to extract PAHs from the soils was a modification of those by Kipopoulou et al (1999), Simonich and Hites (1994), and Gao et al (2005). Specifically, 4 g (dry weight) of the ground soil particles (0.2 mm aperture) were extracted twice using an ultrasonic crusher (JY92-2D, China) with 40 mL of mixed dichloromethane and acetone (5:3 v/v) after the soil samples were soaked overnight in 40 mL of the above solvent.…”
Section: Pah Analyses Of Soil Plant and Solution Samplesmentioning
confidence: 99%
“…Due to carcinogenic, mutagenic, and teratogenic properties (Brady et al, 2003), their occurrence frequency (Jones et al, 1989;Wennrich et al, 2002;Tao et al, 2004) and their environment persistence (Fismes et al, 2002;Bi et al, 2003), PAHs are of a particular concern to human and environmental health. Conceivably, plants could be exploited to aid in the removal of PAHs and other contaminants from soils via two main mechanisms: (1) the accumulation by, and the subsequent metabolism in, plant tissues following the contaminant uptake by plant roots (Fismes et al, 2002;Wild et al, 2005) and (2) the enhanced microbial activity induced by root exudation of enzymes to transform and/or mineralize contaminants (Rentz et al, 2004;Kamath et al, 2005). Thus, the bioavailability of soil associated PAHs and plant uptake capacity would greatly influence the efficiency of PAH phytoremediation.…”
Section: Introductionmentioning
confidence: 99%